FACTORS AFFECTING THE SEXUAL BEHAVIOR OF YOUTH AND ADOLESCENT IN JIMMA TOWN, ETHIOPIA - Kumsa, Diribe Makonene (European Scientific Journal, ESJ, 2015)
Youth and adolescents account for the highest number of population in Ethiopia which can potentially contribute to the development of the country. However, there are several sexual related problems which can hinder them from being productive. Several organizations are working to promote Sexual and Reproductive Health (SRH) services including safe sex practices to reduce the extent of the problems. Most of the previous studies focused on the identifications of negative factors that can hinder adolescents and youth from safe sexual practices. The aim of this study is to identify facilitative factors which can help adolescents to develop their capacity for better decision about safe sexual behavior. These factors are identified at individual, family and organizational levels by using salutogenic approach as a guiding principle. A qualitative cross-sectional study design was used to investigate factors affecting adolescents and youths’ safe sexual behavior by using an in-depth interview and FGD. The results show various facilitative factors at different levels of the community. SRH knowledge and life motives are identified as resources at individual level while strong childrenparental communications are motives at family level. Availability of SRH integrated services and involvements of peer counselors are motivating factors identified at organizational level. These facilitative resources are vital in developing the capacity of the youth and adolescents for safe sexual behavior. Poor parental communication, peer pressure and socioeconomic problems related to youths living departed from their families are identified as barriers. These factors make individuals likely to have less sense of coherence to use the available resources. This study suggests the involvement of parent in youth SRH service promotion to reduce the strong cultural ties distancing children-parental discussion on sex and sexuality.